LEVERAGING ON PARTNERSHIP TO EXPOSE YOUTH TO SUSTAINABLE DEVELOPMENTS: A CASE STUDY (Journal of Business Management and Accounting, 2023)
The Sustainable Development Goals (SDGs) were adopted by the United Nations (UN) in 2015. They are a worldwide call to end poverty, protect the planet, and promote peace and prosperity for everyone by 2030. The 17 SDGs are interconnected and seek to strengthen the social, economic, and environmental dimensions of sustainable development. Malaysia is one of the countries committed to these global goals. In every situation, achieving the SDGs requires collaboration and resources from all parts of society, and youths are the part of the population that is most important in implementing the SDGs. To get young people involved in the planning and building of the country's sustainable development, it is important for different groups to work together. This article examines how partnerships can effectively help an organisation reach its goals and what the most important principles are when forming a partnership.  In this paper, the Malaysian Youth SDG Summit will be used as a case study.  The summit started with the support of 30 youth-based organisations and was backed up by the Malaysian Civil Society Organisation—SDG Alliance and the All-Party Parliamentary Group Malaysia—SDG. The Malaysian Youth SDG Summit, which began as a one-day event, has evolved into a year-long effort to develop the capacity of young people to become SDG competent through the Youth SDG Agent initiative. The study provides information on how to leverage partnerships to expose youth to sustainable developments, drawing on the case from the youth SDG Summit and youth SDG agents. The strength of the partnership has made a big difference in the brand's credibility, its exposure in the media, its network, its support for hardware, and its human resources.